Economic indicators impact to the exchange rate movement of currencies Thai bath against Japanese Yen - Lerdloompheephan, Panwadee (Journal of Humanities and Social Sciences Thonburi University, 2022)
This research aims to study the Economic indicators impact to the exchange rate movement of currencies Thai bath against Japanese Yen from the foreign exchange rate model. Interbank Interest Rate, Net international reserve, Price Index of Imported Products, Value of Thai exports to Japan, Current Account, Balance of Payment as the variables in this study. Using monthly secondary data from January, 2011 until December, 2020 a total of 120 months in total were analyzed by the quantitative analysis. Research instrument was employed Multiple Regression with Ordinary Least Square Method. The result found that the Interbank Interest Rate, Net international reserve, Value of Thai exports to Japan, Current Account were the relationship in the direction of the impact to the exchange rate movement of currencies Thai bath against Japanese Yen by significant statistical. The other factors included the Price Index of Imported Products, Balance of Payment were the relationship in the opposite direction of the exchange rate movement of currencies Thai bath against Japanese Yen by significant.